(untitled) (American Journal of Islam and Society, 2002)
This paper would normally appear in a journal of cartography. We decided, nonetheless, to publish it in AJISS because it well illustrates the need to incorporate interdisciplinary approaches when addressing questions that fall under the category of the Shari’a. The paper reiterates a point often repeated in AJISS and reminds us of the need to redesign the curriculum of Shari’a schools so as to allow the graduates to have a deeper understanding of social and natural phenomena.